2000
DOI: 10.1046/j.1365-2036.2000.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric damage in the rat with nitrogen‐containing bisphosphonates depends on pH

Abstract: Gastric damage potential did not correlate with bone anti-resorptive effects, and the more potent anti-resorptive N-BPs were not necessarily more damaging to the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Although bisphosphonatesinduced gastric damage has been reported in an animal model to be pH dependent with increased damage at increasing pH, ulcerogenic effects of bisphosphonate co-therapy in our clinical setting did not seem to aggravate antisecretory agents that neutralize luminal gastric pH. 48 The mechanisms are unclear, but bisphosphonates-related mucosal damage may change with the doses and types of bisphosphonates and co-therapies.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although bisphosphonatesinduced gastric damage has been reported in an animal model to be pH dependent with increased damage at increasing pH, ulcerogenic effects of bisphosphonate co-therapy in our clinical setting did not seem to aggravate antisecretory agents that neutralize luminal gastric pH. 48 The mechanisms are unclear, but bisphosphonates-related mucosal damage may change with the doses and types of bisphosphonates and co-therapies.…”
Section: Discussionmentioning
confidence: 92%
“…Experimental studies in animal models have indicated that bisphosphonates have the potential to produce gastric mucosal irritation. [18][19][20][21] A number of short-term endoscopy studies have been performed to investigate the association between bisphosphonate treatment and the development of mucosal erosive lesions of the upper gastrointestinal (GI) tract. [22][23][24][25][26][27][28][29] Although the two representative bisphosphonates, alendronate and resedronate, have been demonstrated to have upper gastrointestinal safety and tolerability profi les comparable to those of placebo in large clinical studies, [30][31][32][33][34][35] there have not previously been endoscopic studies in the clinical setting that comprise long-term concomitant use of ulcerogenic agents such as NSAID, corticosteroids, and bisphosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in animal models investigated the physiopathological mechanisms underlying GI AE occurrence after bisphosphonate ingestion, suggesting a direct correlation with low gastric pH [41,42]. The correlation between GI AE with increased pH and inflammation has been confirmed in these models using gastro protective and anti-inflammatory agents, showing a decrease in the occurrence and magnitude of these AE [43][44][45][46][47][48].…”
Section: New Alendronate Formulationmentioning
confidence: 94%
“…Similarly, it is well established that GI irritation is a common side effect of BP treatment. An interesting finding regarding GI irritation with BP is that these effects are enhanced in alkaline environments (9). These findings indicate separate effects of BP on membrane transport as well as paracellular transport processes, especially in GI epithelia, in which a barrier function is dependent on an intact (high resistance) paracellular pathway (for review, see Ref.…”
mentioning
confidence: 98%